GENERASI MUDA KRISTIANI DALAM MENELADANI YESUS SEBAGAI GURU DAN PEMIMPIN MASA KINI - Juniati Reski Bali; Florians Datu Toding, Nengsi Musu’, Yohanis, Tadius Ta’dung (CV. ADIBA AISHA AMIRA, 2023)
This research aims to explore the understanding and practices of young Christian generations in their efforts to emulate Jesus as a teacher and leader in the context of modern society. The study will analyze how young Christians apply the teachings and values taught by Jesus Christ in their daily lives and in their leadership roles within the church and society. The research method employed is qualitative research, with data collection through document analysis. The gathered data will be analyzed using a thematic approach to identify patterns of understanding and practices. The results of this research are expected to provide a better understanding of how young Christians confront challenges and opportunities in emulating Jesus as a teacher and leader in the context of modern society. Additionally, this research is also expected to offer insights for the church and church leaders in supporting and guiding young Christian generations on their journey to becoming leaders inspired by the teachings of Jesus Christ.